Root Cause Analysis for Identifying Defects in the Process of Cylinder Head Castings from Aluminium Alloy - Kalincova, Daniela; Tavodova, Miroslava; Cierna, Helena (Manufacturing Technology Journal, 2015)
The research into root causes of defects in cylinder head castings are described in the paper. Chemical composition of castings, evaluation of casting microstructure before and after the heat treatment and final inspection of casting quality from various points of view are parts of the research. The list of the most common defects in case of using five selected products is the result of the experiment. The objective of the research was to identify causes of defects in the process of cylinder head casting as well as to identify root causes of discrepancy using the quality management tool.
Keywords: cylinder head; casting; defect; management quality tools